OPPORTUNISTIC INFECTIONS WITH ORAL INJURIES IN HIV-INFECTED PATIENTS BEFORE PRESCRIPTION AND AGAINST THE BACKGROUND OF ANTIRETROVIRAL THERAPY - Marchenko, K.V.; Koval, T.I.; Marchenko, O.H.; Dvornyk, V.M. (World of Medicine and Biology, 2021)
The study included 181 HIV-infected patients (127 men and 54 women) aged 21 to 55 years (mean 34.6±7.01 years). Follow-up of HIV-infected patients from the time of registration to ART lasted an average of 1.64±0.17 years. The study showed that at the time of ART initiation, the majority of HIV-infected patients – 148 (81.8 %) – were dominated by the 3rd and 4th clinical stages with the registration of opportunistic infections inherent in these stages, respectively. In particular, oropharyngeal candidiasis was observed in half of the examined patients – 76 (42.0 %), and oral hairy leukoplakia in – 49 (27.0 %) patients, and in some of the examined patients, the level of CD4 lymphocytes exceeded 350 cells/µL. Despite antiretroviral therapy’s high overall virological and immunological efficacy in 11 (6.0 %) patients, opportunistic infections with oral lesions were recorded at CD4 lymphocyte counts ≥350 cells/µL.